Comparing numerical methods for solving Chaotic and Stiff Initial Value Problems (IVPs) - Chowdhury, Md. Sazzad Hossien (2018)
In this talk, I will show some results for solving Chaotic and Stiff IVPs by the standard homotopy perturbation method (HPM) and the multi-stage homotopy perturbation method, the classical Adomian decomposition method (ADM), the multi-stage Adomian decomposition method (MADM) and an explicit Runge-Kutta type method (RK). Numerical comparisons demonstrate the limitations of the standard HPM and ADM and promising capability of the MHPM and MADM for solving Chaotic and Stiff IVPs